Precarious Drop : Reassessing Patterns of Female Labor Force Participation in India - Andres, Luis A. (World Bank, Washington, DC, 2017)
This paper uses successive rounds of National Sample Survey Organization data from 1993-94 to 2011-12, and draws from census data. This paper (i) provides a description of nearly two decades of patterns and trends in female labor force participation in India; (ii) estimates the extent of the recent decline in female labor force participation; and (iii) examines and assesses the contribution of various demographic and socioeconomic factors in explaining the female labor force participation decision and the recent the drop. The analysis finds that female labor force participation dropped by 19.6 million women from 2004–05 to 2011–12. Participation declined by 11.4 percent, from 42.6 to 31.2 percent during 1993–94 to 2011–12. Approximately 53 percent of this drop occurred in rural India, among those ages 15 to 24 years. Factors such as educational attainment, socioeconomic status, and household composition largely contributed to the drop, although their effects were more pronounced in rural areas. Specifically, the analysis finds a U-shaped relationship between levels of educational attainment and female labor force participation. The decomposition of the contribution of these various determinants to the female labor force participation decision suggests that stability in family income, as indicated by the increasing share of regular wage earners and declining share of casual labor in the composition of family labor supply, has led female family members to choose dropping out of, rather than joining, the labor force. The findings of this paper suggest that conventional approaches to increasing female labor force participation (such as education and skills and legal provisions) will be insufficient. Policies should center on promoting the acceptability of female employment and investing in growing economic sectors that are more attractive for female employment.